Using Google Workspace for Education to Engage Accounting Students - Nurkhin, Ahmad; Rohman, Abdul (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2023)
This study aimed to describe the level of student engagement in online and face-to-face learning. This study also aimed to describe learning innovations created by lecturers by utilizing existing features on Google workspace. Finally, this study offers suggestions for using Google Workspace in accounting learning to improve student engagement. Quantitative and qualitative descriptive research was conducted by observing the experiences of students and lecturers during post-pandemic face-to-face learning. Questionnaires, observations, and interviews were used to gather data. The data analysis method used was quantitative and qualitative descriptive analysis. The results of the study indicated that there was no lack of student engagement in face-to-face learning. Lecturers had utilized the features on Google workspace but not optimally. Google's most frequently used service features were Google Classroom, YouTube, and Google Drive. Meanwhile, Google site, Jamboard and podcasts were the services that were rarely used. Lecturers could utilize google docs, google sheets, and google slides for accounting learning so that student engagement could increase significantly. This feature required students to actively collaborate to complete assignments because lecturers could monitor activities carried out by students in real time.